Simulation and Experimental Study on Rock-Breaking Mechanism of the Reverse Rotary Torque Self-balancing Dual Drill Bit - Zhang, Cong; Gao, Ke; Zhao, Yan; Xie, Xiaobo; Zhang, Congshan; Lv, Xiaoshu (Springer, 2023)
The stick–slip vibration of a drill bit in oil and gas drilling causes significant disturbances to the formation, severely impacting the drilling quality. The dual drill bit (DB) torque self-balancing drilling technology has superior drill bit stability, obtained by balancing the torques of the inner and outer bits (IB and OB). However, research on the DB working process is still in the initial stages. To analyze the vibration reduction in the DB from the perspective of the rock-breaking mechanism, this study established a dynamic rock-breaking finite element model of the DB through theoretical calculations and conducted a numerical simulation comparison and drilling experiment comparison of the rock-breaking process between the DB and conventional drill bit (CB). The differences in the reactive torque between the DB and CB were compared. Subsequently, the drilling process was simulated using the two drilling methods, including the rock-breaking process, core and wellbore disturbance, and bit motion. The results indicate that DB drilling can reduce the torque vibration of the rock on the drill bit by 69.7%, thus decreasing the damage to the formation. In addition, DB can form a shear-breaking effect on the rock at the junction of IB and OB, which improves the rock-breaking efficiency by 13.8%. The results of this work will help reveal the low stick–slip vibration mechanism of the DB self-balancing drilling technique, which can provide new ideas for the study of drilling stability.
Keywords: Torque self-balancing dual drill bit; Rock-breaking mechanism; Stick–slip vibration; Drilling stability; fi=Energiatekniikka|en=Energy Technology|